Characterization of Heavily Irradiated Dielectrics for Pixel Sensors Coupling Insulator Applications - Bharthuar, S.; Golovleva, M.; Bezak, M.; Brücken, E.; Gädda, A.; Härkönen, J.; Karadzhinova-Ferrer, A.; Kramarenko, N.; Kirschenmann, S.; Koponen, P.; Luukka, P.; Mizohata, K.; et al. (Frontiers in Materials, 2022)
An increase in the radiation levels during the high-luminosity operation of the Large Hadron Collider (LHC) calls for the development of silicon-based pixel detectors that are used for particle tracking and vertex reconstruction. Unlike the conventionally used conductively coupled (DC-coupled) detectors that are prone to an increment in leakage currents due to radiation, capacitively-coupled (AC-coupled) detectors are anticipated to be in operation in future collider experiments suitable for tracking purposes. The implementation of AC-coupling to micro-scale pixel sensor areas enables one to provide an enhanced isolation of radiation-induced leakage currents. The motivation of this study is the development of new generation capacitively coupled (AC-coupled) pixel sensors with coupling insulators having good dielectric strength and radiation hardness simultaneously. The AC-coupling insulator thin films were aluminum oxide (Al2O3) and hafnium oxide (HfO2) grown by Atomic Layer Deposition (ALD) method. A comparison study was performed based on the dielectric material used in MOS, MOSFET and AC-coupled pixel prototypes processed on high resistivity p-type Magnetic Czochralski silicon (MCz-Si) substrates. Post-irradiation studies with 10 MeV protons up to a fluence of 1015 protons/cm2 suggest hafnium oxide to be a better candidate as it provides higher sensitivity with negative charge accumulation on irradiation. Further, even though the nature of the dielectric does not affect the electric field within the AC-coupled pixel sensor, samples with hafnium oxide are comparatively less susceptible to undergo an early breakdown due to irradiation. Edge-Transient Current Technique (e-TCT) measurements show a prominent double junction effect as expected in heavily irradiated p-type detectors, in accordance with the simulation studies.